Decision Making in the Release of Freshwater Turtles and Tortoises - Innis, Charles (Wildlife Rehabilitation Bulletin, 2017)
Chelonians are the most frequent reptiles presented to wildlife rehabilitators. While they are often able to recover from very severe injuries, this may be a prolonged process involving months to years of care. Major factors in deciding when and where to release rehabilitated chelonians include population demographics, extent of injuries, locality data of the specimen, infectious disease transmission, legal issues, the likelihood of future reproduction, healing ability in the wild vs. captivity, and time of year.